Specific Integration of Temperate Phage Decreases the Pathogenicity of Host Bacteria - Chen, Yibao; Yang, Lan; Yang, Dan; Song, Jiaoyang; Wang, Can; Sun, Erchao; Gu, Changqin; Chen, Huanchun; Tong, Yigang; Tao, Pan; Wu, Bin (Frontiers in Cellular and Infection Microbiology, 2020)
Temperate phages are considered as natural vectors for gene transmission among bacteria due to the ability to integrate their genomes into a host chromosome, therefore, affect the fitness and phenotype of host bacteria. Many virulence genes of pathogenic bacteria were identified in temperate phage genomes, supporting the concept that temperate phages play important roles in increasing the bacterial pathogenicity through delivery of the virulence genes. However, little is known about the roles of temperate phages in attenuation of bacterial virulence. Here, we report a novel Bordetella bronchiseptica temperate phage, vB_BbrS_PHB09 (PHB09), which has a 42,129-bp dsDNA genome with a G+C content of 62.8%. Phylogenetic analysis based on large terminase subunit indicated that phage PHB09 represented a new member of the family Siphoviridae. The genome of PHB09 contains genes encoding lysogen-associated proteins, including integrase and cI protein. The integration site of PHB09 is specifically located within a pilin gene of B. bronchiseptica. Importantly, we found that the integration of phage PHB09 significantly decreased the virulence of parental strain B. bronchiseptica Bb01 in mice, most likely through disruption the expression of pilin gene. Moreover, a single shot of the prophage bearing B. bronchiseptica strain completely protected mice against lethal challenge with wild-type virulent B. bronchiseptica, indicating the vaccine potential of lysogenized strain. Our findings not only indicate the complicated roles of temperate phages in bacterial virulence other than simple delivery of virulent genes but also provide a potential strategy for developing bacterial vaccines.